Description and prediction of outcome of drowning patients in New South Wales, Australia: protocol for a data linkage study. Issue 1 (15th January 2021) - Peden, Amy E; Sarrami, Pooria; Dinh, Michael; Lassen, Christine; Hall, Benjamin; Alkhouri, Hatem; Daniel, Lovana; Burns, Brian
Abstract : Introduction: Despite being a preventable cause of death, drowning is a global public health threat. Australia records an average of 288 unintentional drowning deaths per year; an estimated annual economic burden of 1.24 billion AUD (2017). On average, a further 712 hospitalisations occur due to non-fatal drowning annually. The Australian state of New South Wales (NSW) is the most populous and accounts for 34% of the average fatal drowning burden. This study aims to explore the demographics and outcome of patients who are admitted to hospitals for drowning in NSW and also investigates prediction of patients' outcome based on accessible data. Methods and analysis: This protocol describes a retrospective, cross-sectional data linkage study across secondary data sources for any person (adult or paediatric) who was transferred by NSW Ambulance services and/or admitted to a NSW hospital for fatal or non-fatal drowning between 1/1/2010 and 31/12/2019. The NSW Admitted Patient Data Collection will provide data on admitted patients' characteristics and provided care in NSW hospitals. In order to map patients' pathways of care, data will be linked with NSW Ambulance Data Collection and the NSW Emergency Department Data Collection. Finally patient's mortality will be assessed via linkage with NSW Mortality data, which is made up of the NSW Register of Births, Deaths and Marriages and a Cause of Death Unit Record File. Regression analyses will be used to identify predicting values of independent variables with study outcomes. Ethics and dissemination: This study has been approved by the NSW Population & Health Services Research Ethics Committee. Results will be disseminated through peer-reviewed publications, mass media releases and at academic conferences. The study will provide outcome data for drowning patients across NSW and study results will provide data to deliver evidence-informed recommendations for improving patient care, including updating relevant guidelines.